Kompetensi Kepribadian Guru Pendidikan Anak Usia Dini dalam Mengembangkan Nilai Agama dan Moral - Nazipah, Nurul (Journal of Educational Research, 2023)
This article discusses teacher personality competencies in developing religious and moral values in Islamic Kindergartens in Jambi City. The main problem studied is how teachers' personality competencies develop religious and moral values in students aged 5 to 6 years. This article comes from qualitative research by extracting data through observation, interviews and documentation. The research results show that the teacher's personality competence has not become a role model in the form of actions carried out by students. This deficiency does not solely lie in the teacher's personal competence, but also the weak support from various parties in the school ecosystem, starting from the principal, teachers and parents of students. Artikel ini membahas kompetensi kepribadian guru dalam pengembangan nilai-nilai agama dan moral di Taman Kanak-Kanak Islam di Kota Jambi. Permasalahan utama yang dikaji adalah bagaimana kompetensi kepribadian guru dalam  mengembangkan nilai-nilai agama dan moral pada peserta didik yang berusia 5 sampai 6 tahun. artikel ini berasal dari penelitian kualitatif dengan penggalian data secara observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa kompetensi kepribadian guru belum menjadi role model dalam bentuk tindakan yang dilakukan anak didik.  Kekurangan ini bukan semata-mata terletak pada kompetensi kepribadian gurunya, namun juga lemahnya dukungan dari berbagai pihak yang menjadi ekosistem sekolah, mulai dari kepala sekolah, guru, dan orang tua peserta didik.